2007
DOI: 10.1128/ec.00338-06
|View full text |Cite
|
Sign up to set email alerts
|

Genome Survey Sequencing of the Wine Spoilage YeastDekkera (Brettanomyces) bruxellensis

Abstract: The hemiascomycete yeast Dekkera bruxellensis, also known as Brettanomyces bruxellensis, is a major cause of wine spoilage worldwide. Wines infected with D. bruxellensis develop distinctive, unpleasant aromas due to volatile phenols produced by this species, which is highly ethanol tolerant and facultatively anaerobic. Despite its importance, however, D. bruxellensis has been poorly genetically characterized until now. We performed genome survey sequencing of a wine strain of D. bruxellensis to obtain 0.4؋ cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
136
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(144 citation statements)
references
References 67 publications
3
136
2
3
Order By: Relevance
“…Further, sugars such as arabinose, lactose, and raffinose did not support the growth of most isolates (2). Woolfit et al (22) reported the presence of five genes involved in nitrate assimilation in B. bruxellensis CBS 2499, including genes encoding a nitrate reductase, a nitrite reductase, and a nitrate transporter, as well as two regulatory genes encoding a Zn(II) 2 Cys 6 transcriptional factor for nitrate induction. Strains of Hansenula polymorpha in which any of these genes were disrupted lost their ability to grow on nitrate (64,69,70), showing their necessity in the assimilation of nitrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, sugars such as arabinose, lactose, and raffinose did not support the growth of most isolates (2). Woolfit et al (22) reported the presence of five genes involved in nitrate assimilation in B. bruxellensis CBS 2499, including genes encoding a nitrate reductase, a nitrite reductase, and a nitrate transporter, as well as two regulatory genes encoding a Zn(II) 2 Cys 6 transcriptional factor for nitrate induction. Strains of Hansenula polymorpha in which any of these genes were disrupted lost their ability to grow on nitrate (64,69,70), showing their necessity in the assimilation of nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…Woolfit et al reported a partial genome sequence of a B. bruxellensis wine contaminant (CBS 2499) and identified approximately 3,000 genes (22). Recently, the full genome sequence of this strain was determined and used to deduce the genetic background of some food-relevant properties and the evolutionary history of this yeast (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze species-specific sequence variation, five regions from the D. bruxellensis sequence were randomly chosen (40) a The Centraalbureau Vor Schimmelcultures (CBS) collection of Dekkera bruxellensis strains was used in this study. Shown are GenBank accession numbers for nuclear 26S rDNA (D1/D2 fragment) and mitochondrial 15S rDNA.…”
Section: Methodsmentioning
confidence: 99%
“…The lineages of D. bruxellensis and S. cerevisiae separated at approximately the same time as the lineages of S. cerevisiae and C. albicans separated, approximately 200 million years ago (40). However, D. bruxellensis and S. cerevisiae share several characteristics, such as the production of ethanol, the ability to propagate in the absence of oxygen (anaerobic growth), and petite positivity (the ability to produce offspring without mitochondrial DNA [mtDNA]), that are rarely found among other yeasts (16,20).…”
mentioning
confidence: 99%